(untitled) (Revista Electrónica REDINE, 2020)
The objective of the investigation was to determine the level of investigative competences that teachers possess in the San Francisco Javier de Barquisimeto National Educational Unit, Iribarren municipality, Lara state. The methodology is field, descriptive. The study population consisted of 60 teachers. The data collection technique was a structured questionnaire. It was validated by expert judgment and its reliability was calculated with the Cronbach’s alpha coefficient, giving a result of 0.96 (very high reliability). It was determined that teachers have low investigative productivity and a medium level of primary instrumental cognitive skills to perform their role as researchers. It is recommended to carry out a training program to develop investigative skills.